PENERAPAN SISTEM BAGI HASIL PADA TABUNGAN MUDHARABAH PADA BMT-MMU PASURUAN - Aisyah, Esy Nur (Faculty of Economics Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2013)
In the case of gathering the society fund through Mudharabah saving, need standards of operational procedure by BMT (inverse) and the members of a cooperative (Inventory) as a frame work seriously to provide a professional human resource. The profit of both of them have to decided before when made agreement. The profit comparative of profit sharing depend on factors influenced the small big of profit sharing. This study is qualitative research by using a descriptive method that supposed to describe the application of profit sharing, and the factors influenced the small big of profit sharing. In addition, it will analyze the application problems and provide the alternative problem solving. To get a data validity on this study, the writer use a qualitative analysis by triangulation as a technical data analysis. Keywords: profit sharing, tabungan mudharabah